Strategi Pembatasan Kunjungan Ke Bali sebagai Upaya Pelestarian Budaya Lokal - Jansen Stepanus; Komang Febrinayanti Dantes; I Gusti Ayu Apsari Hadi; I Nusti Ngurah Budiyasa (Pemuliaan Keadilan, 2026)
Bali is globally renowned not only for its natural beauty but also for its rich cultural heritage. However, the island's growing popularity as a tourist destination has led to increasing concerns over the erosion of its local traditions and values. This study explores the concept of restricting visitor numbers as a strategic effort to preserve Bali’s cultural identity. Using a qualitative approach that includes literature review and in-depth interviews with cultural practitioners, local traditional leaders, and sustainable tourism stakeholders, this research reveals that well-managed visitor restrictions can create a more sustainable balance between tourism and cultural preservation. Key strategies include setting visitor quotas, implementing culturally-focused entry requirements, and fostering cooperation between local government and traditional communities to determine cultural carrying capacity. The findings suggest that cultural conservation and tourism development are not mutually exclusive when managed with a shared vision of sustainability. This paper advocates for a cultural-based tourism policy that prioritizes quality over quantity, ensuring that Bali remains a living heritage for future generations.